An Introduction to Sequential Dynamical Systems - Mortveit, Henning S. (Springer, 2017)
Preface -- What is a Sequential Dynamical System?- A Comparative Study -- Graphs, Groups, and Dynamical Systems -- Sequential Dynamical Systems over Permutations -- Phase-Space Structure of SDS and Special Systems -- Graphs, Groups, and SDS -- Combinatorics of Sequential Dynamical Systems over Words -- Outlook -- References -- Index.